Effects of climate change and anthropogenic modification on a disturbance‐dependent species in a large riverine system. Issue 1 (11th January 2017) - Zeigler, Sara L.; Catlin, Daniel H.; Bomberger Brown, Mary; Fraser, James D.; Dinan, Lauren R.; Hunt, Kelsi L.; Jorgensen, Joel G.; Karpanty, Sarah M.
Abstract: Humans have altered nearly every natural disturbance regime on the planet through climate and land‐use change, and in many instances, these processes may have interacting effects. For example, projected shifts in temperature and precipitation will likely influence disturbance regimes already affected by anthropogenic fire suppression or river impoundments. Understanding how disturbance‐dependent species respond to complex and interacting environmental changes is important for conservation efforts. Using field‐based demographic and movement rates, we conducted a metapopulation viability analysis for piping plovers ( Charadrius melodus ), a threatened disturbance‐dependent species, along the Missouri and Platte rivers in the Great Plains of North America. Our aim was to better understand current and projected future metapopulation dynamics given that natural disturbances (flooding or high‐flow events) have been greatly reduced by river impoundments and that climate change could further alter the disturbance regime. Although metapopulation abundance has been substantially reduced under the current suppressed disturbance regime (high‐flow return interval 20 yr), it could grow if the frequency of high‐flow events increases as predicted under likely climate change scenarios. We found that a four‐year return interval would maximize metapopulation abundance, and all subpopulations in the metapopulation would act as sources at a return interval of 15 yr or less. Regardless of disturbance frequency, the presence of even a small, stable source subpopulation buffered the metapopulation and sustained a low metapopulation extinction risk. Therefore, climate change could have positive effects in ecosystems where disturbances have been anthropogenically suppressed when climatic shifts move disturbance regimes toward more historical patterns. Furthermore, stable source populations, even if unintentionally maintained through anthropogenic activities, may be critical for the persistence of metapopulations of early‐successional species under both suppressed disturbance regimes and disturbance regimes where climate change has further altered disturbance frequency or scope.